2019
DOI: 10.3389/fpsyg.2019.01285
|View full text |Cite
|
Sign up to set email alerts
|

Far-Transfer Effects of Strategy-Based Working Memory Training

Abstract: We assessed the transfer effects of training working memory strategies to a novel problem-solving task. Previous WM training studies have produced little evidence for transfer across contexts. In the current study, 64 6- to 9-year-olds were randomly assigned to one of four training conditions: semantic and rehearsal training, semantic training only, rehearsal training only, and treated control group. All training groups performed significantly better on the transfer task than the control group, but training gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…Moreover, as these studies demonstrated, working memory training can be embedded relatively easily into existing evidence‐based reading instruction, curricula, and activities, suggesting that the element model may have the potential to provide a cost‐efficient, promising reading intervention framework, especially for struggling readers who show little response even to very intensive evidence‐based reading instruction. Nevertheless, more experimental studies are needed to further evaluate this model, possibly by considering other cognitive skills (e.g., updating, switching, inhibition in executive function) and strategies (e.g., semantic linking) shared between reading and cognitive tasks (Chan, Mueller, & Masson, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as these studies demonstrated, working memory training can be embedded relatively easily into existing evidence‐based reading instruction, curricula, and activities, suggesting that the element model may have the potential to provide a cost‐efficient, promising reading intervention framework, especially for struggling readers who show little response even to very intensive evidence‐based reading instruction. Nevertheless, more experimental studies are needed to further evaluate this model, possibly by considering other cognitive skills (e.g., updating, switching, inhibition in executive function) and strategies (e.g., semantic linking) shared between reading and cognitive tasks (Chan, Mueller, & Masson, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The auditory tones are the stimuli to induce MMN; thus, there is a limit of the performance of the WM effect with regard to the visual and auditory digits. Previous studies have shown an impact of the stimulation task type training on the WM types (Chan et al, 2019 ; Linares et al, 2019 ). A behavior study showed that enhanced transfer of the auditory discrimination learning is mediated by WM, which reflects that WM updating is related to fine auditory discrimination (Zhang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 95%
“…A more comprehensive intervention that includes cognitive training in multiple cognitive domains and/or cognitive training in combination with other lifestyle interventions (e.g., diet, physical activity, and blood pressure management) may have a stronger impact on mortality risk. Single-domain cognitive training and multi-domain training may differ in transfer effects, with the latter potentially contributing more to far transfer effects (generalization of training effects to tasks dissimilar from training tasks) compared to near transfer effects (improvement on tasks very similar to training tasks) more robustly (Barnett & Ceci, 2002; Chan et al, 2019; Wolinsky et al, 2016).…”
Section: Discussionmentioning
confidence: 99%